2021
DOI: 10.21733/ibad.852211
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarında Kariyer Yetkinlik Beklentisi ve Mesleki Sonuç Beklentisi: Kariyer Stresinin Aracı Rolü

Abstract: Bu araştırmanın amacı öğretmen adaylarının kariyer yetkinlik beklentisi ve mesleki sonuç beklentisi arasındaki ilişkide kariyer stresinin aracı rolünün incelenmesidir. Araştırmanın örneklemini bir devlet üniversitesinde lisans eğitimine devam eden 377 kişi oluşturmaktadır. Araştırmada veri toplama araçları olarak; Mesleki Sonuç Beklentileri Ölçeği, Kariyer Kararı Yetkinlik Beklentisi Ölçeği Kısa Formu, Kariyer Stresi Ölçeği ve kişisel bilgi formu kullanılmıştır. Yapısal eşitlik modeli sonucu elde edilen bulgul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…There were negative correlations between students' career decision-making selfefficacies and career stress and positive correlations between students' career decision-making selfefficacies and the level of family influence on career decision. Gürpınar et al, (2021) examined the correlation between university students' career decision competence expectations and career stress and concluded that as students had high career decision-making self-efficacies, their ability to cope with stressful situations increased, that is, their levels of career stress decreased. The results of the aforementioned study are compatible with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…There were negative correlations between students' career decision-making selfefficacies and career stress and positive correlations between students' career decision-making selfefficacies and the level of family influence on career decision. Gürpınar et al, (2021) examined the correlation between university students' career decision competence expectations and career stress and concluded that as students had high career decision-making self-efficacies, their ability to cope with stressful situations increased, that is, their levels of career stress decreased. The results of the aforementioned study are compatible with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%